2022
DOI: 10.3389/fpubh.2022.999354
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following immunization of COVID-19 vaccine among children aged 6–11 years

Abstract: IntroductionStarting in December 2021, the Indonesian Government has recommended inactivated SARS-CoV-2 vaccine (CoronaVac) for children aged 6–11 years. This study aims to determine the prevalence and determinant factors of adverse events following immunization (AEFI) of the first dose and the second dose of the COVID-19 vaccine among children aged 6–11 years old.Materials and methodsWe conducted a cross-sectional study in Bantul District, Yogyakarta, Indonesia, in February–March 2022. Data were collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…12, No. 3, September 2023: 924-931 930 the AEFI incidence of the COVID-19 vaccine at doses 1 and 2 was comparable to the trial results and in the community [27]. Other studies, on the other hand, found that because they had AEFI at dose 1, people were hesitant to receive dose 2 [9], [16], [28], [29].…”
Section: Discussionsupporting
confidence: 59%
“…12, No. 3, September 2023: 924-931 930 the AEFI incidence of the COVID-19 vaccine at doses 1 and 2 was comparable to the trial results and in the community [27]. Other studies, on the other hand, found that because they had AEFI at dose 1, people were hesitant to receive dose 2 [9], [16], [28], [29].…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, most vaccine reactions are minor and subside on their own (WHO). During crises such as Covid-19, the prevalence of AEFI in the Covid-19 vaccination among schoolage children in Indonesia was mostly mild and comparable to the risk that has been reported during the vaccine trial (52). In addition, in terms of cost, economic evaluation showed that the cost of AEFI per vaccine could reached 150 times less than the average cost per disease (53).…”
Section: Utilitarianismmentioning
confidence: 62%
“…The prevalence of fever was lowest in children aged 5-11 years, 2.9% after dose 1 and 4.9% after dose 2, and was higher in older adolescents. [10][11][12][14][15][16][17] At doses 1 and 2, most of them received the Sinovac vaccine. The most common symptoms felt were drowsiness, local swelling and pain, and a feeling of weakness and weakness.…”
Section: Discussionmentioning
confidence: 99%